Catalytic Oxidation of CO and CH4 over Hexaaluminate based Catalysts : Catalytic Oxidation of CO and CH4 over Hexaaluminate based Catalysts - Butt , Saad (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
In this work, hexaaluminate based catalysts – namely LaMnAl11O19 andPd/LaMnAl11O19 were tested for catalytic oxidation of a model gas comprising of a mixture of CO and CH4. The co-precipitation route was employed to synthesize both catalyst sample sowing to better chances of attaining higher surface areas at higher calcination temperatures. The N2 adsorption isotherms yielded surface areas of 20 and 14 m2/g for LaMnAl11O19 and Pd/LaMnAl11O19 respectively. TheT90of CO (temperature at 90% conversion) were recorded at 482 °C and 185 °C for LaMnAl11O19 and Pd/LaMnAl11O19 respectively. Moreover, a methane conversion of 62 % at 700 °C was achieved over Pd/LaMnAl11O19 in comparison to only 28 % in case of LaMnAl11O19. The structural characterisation showed that a better mobility of oxygen atoms in the lattice structure of Pd/LaMnAl11O19 along with a more pronounced mass transport phenomenon yielded a better conversion of CO and CH4 at relatively low temperatures.